The Big Man Muqtada al-Sadr: Leading the Street in Iraq under Limited Statehood. Issue 3 (1st November 2020) - Selvik, Kjetil; Amirteimour, Iman
ABSTRACT: The article conceptualises the Shia cleric Muqtada al-Sadr as a big man to explain his proven capability for navigating the hazardous terrain of Iraqi politics. Introduced in Sahlins' anthropology on Melanesia and refined in African studies, the notion of the big man has been underexploited in accounts of the Arab region. This article defends its relevance for sociopolitical analyses of Iraq and for the study of religious actors. Personal authority is the defining characteristic of a big man, and the mobilisation of followers is the key to his renown. In situations of limited statehood, the ability to build support upon extra-institutional foundations can yield long-lasting political results. Muqtada al-Sadr has relied on an exceptional combination of resources to establish himself as a kingmaker on the political scene. We trace the roots of his ascent and foreground the strategies he has used to accumulate authority in his person. The article analyses Muqtada's response to the wave of popular protests that swept Southern Iraq in 2019, observing a shift from initial support to open confrontation with the demonstrators. We argue that this shift threatens his status because it undermines his most important power resource: the ability to lead the street.